Chapter 4 Choreographing Love Balletic Contact in Sasha Waltz's Roméo et Juliette - Kellermann, Jonas (Taylor & Francis, 2021)
This chapter examines Sasha Waltz's choreographic staging of Berlioz's Roméo et Juliette for the Paris Opera Ballet from 2007. Waltz's production reimagines one of the most canonical stories in the classical ballet repertoire through the abstract and fragmentary lens of contemporary dance. I trace how Waltz appropriates the post-modern principles of Contact Improvisation for purposes of balletic storytelling. Drawing from recent affect-focussed criticism in dance studies, I explore how Waltz uses the non-narrative relationality of Contact Improvisation to transform Shakespeare's poetic constellations of affect into abstract, yet dramatically expressive choreographic embodiments of affect, especially in the Pas de deux during the "Scène d'amour".